KONSEPSI KULTURAL ETNIK MADURA DI WILAYAH EKSKARESIDENAN BESUKI TENTANG SAKIT, PENYAKIT, DAN PENGOBATANNYA - IG. Krisnadi (LITERASI: Indonesian Journal of Humanities, 2014)
The problems discussed in this article are: (1) the cultural conception of Madurese community on illnesses, diseases, and treatments; (2) the creation of a healthy lifestyle among the Madurese communities along the Watershed (DAS) in the region of former residencyt of Besuki. This article aims to understand the views, knowledge, and beliefs regarding illness and disease. It elaborates the Madurese communities’s views on the causes of illnesses, handling and treatments, and their views on healthy lifestyles. It is shown that misconceptions about illnesses, their causes and health have formed an unhealthy lifestyle. There has been a shift in sociocultural conceptions of illness, disease, and health among them. Their sociocultural conceptions of illness, diseases, and health linked to magical beliefs have reduced and they become more rational in their view of sickness, disease, and health. This occurs in harmony with the higher level of education, welfare, and social status. Keywords: cultural conception, illness, disease, treatment